Nursing Students' Experience in Online Learning During Covid-19: Study Phenomenology - Adventina Delima Hutapea; Eva Chris Veronica Gultom; Tirolyn Panjaitan; Deony Aktivini Damainov (Fakultas Keperawatan Universitas Andalas, 2025)
The incidence of COVID-19 has resulted in many policy changes in each country. Some things done are physical distancing, social distancing, and social containment. The Indonesian government implemented Large-Scale Social Restrictions, changes in the school system, and lectures to an online system, worship at home, and work at home. Implementing online learning has obstacles, especially for nursing students, such as ineffective practice, not understanding the material, poor network, limited quota, and even the emergence of stress due to the system. Aim: This study aimed to explore nursing students' experiences in undergoing online learning during COVID-19. This research design uses qualitative research with a phenomenological approach. The number of participants in this study was 14 from two nursing faculties in Jakarta, and the data were saturated using purposive sampling. Data were collected by in-depth interviews using the Zoom platform for 45-60 minutes, then verbatim and analyzed using Collaizi. The results of this study consist of three themes, namely challenges to undergoing online learning, the advantages of online learning, and online learning impacts. The results of this study can be recommended to modify teaching methods, such as inserting interactive material to motivate students to be more interactive and not trigger students to increase independent learning methods. Keywords: Covid-19; Education, distance; Nursing, students; online learning; Physical Distancing